THE NECESSITY AND IMPORTANCE OF THEOLOGICAL ENGAGEMENT WITH NON-MUSLIMS FOR SINGAPORE MUSLIM COMMUNITY - Hassan, Muhammad Haniff Bin (Journal of Al-Tamaddun, 2020)
This paper argues the importance and necessity for Singapore Muslims to be actively involved in theological engagement with non-Muslims in the form of dialogue on theological, social and historical grounds. Theologically, the paper argues that Islam not only permits but also encourages Muslims to engage in dialogue with non-Muslims on theological issues. At a societal level, being a Muslim minority in a secular country and multi-cultural society, the preservation and pursuance of their interest would partly rely on how they relate with and how they are perceived by the larger diverse non-Muslim communities. It is in their interest to actively engage and have dialogue with other communities. Historically and more importantly, Muslim involvement in inter-faith dialogue preserves the legacy left behind by Maulana Abdul Aleem Siddique who pioneered the inter-faith work in Singapore through the founding of the Singapore Inter-Religious Organisation. The paper also refutes those who oppose inter-faith dialogue theologically and those who discourage Muslim involvement for fear of falling into the government’s political agenda. The primary research methodology employed by the paper is through literature review of primary and secondary materials. It also employs interviews of local activists and professionals in inter-faith work as a secondary methodology.